Selisistat, a SIRT1 inhibitor, enhances paclitaxel activity in luminal and triple-negative breast cancer: in silico, in vitro, and in vivo studies - Anna Wawruszak (Journal of Enzyme Inhibition and Medicinal Chemistry, 2025)
Sirtuins (SIRTs) are NAD+-dependent histone deacetylases, which play a key role in cancer progression; however, their prognostic values in breast cancer (BC) remain a subject of debate and controversy. Accumulative evidence suggests that each sirtuin possesses individual character, implicating its role in the regulation of multifaceted biological functions leading to BC initiation, progression and metastasis. Selisistat (EX527) is a potent, cell permeable, highly selective SIRT1 inhibitor. In the study, the tumour-suppressive effects of the SIRT1 inhibitor EX527 (selisistat) alone and in combination with paclitaxel (PAX) in different breast cancer cell lines and zebrafish xenograft models were investigated. The type of pharmacological drug-drug interaction between EX527 and PAX was determined using the isobolographic method. EX527 and PAX used individually inhibited proliferation, induced apoptosis and caused cell cycle arrest in G1 and subG1/G2 phases. Interestingly, the combination of these compounds used in the 1:1 dose-ratio augmented all these effects (IC50add 29.52 ± 3.29 − 38.45 ± 5.26). The co-treatment of EX527 with PAX generated desirable additive drug-drug interaction. The simultaneous application of EX527 and PAX induced a stronger inhibition of tumour growth compared to individual treatments in zebrafish xenografts. In silico analysis revealed a protein-protein interaction pathway (SIRT1-AKT-S1PR1-GNAI1/GNAO1-Tubulin) connecting molecular targets of both ligands. To summarise, the combination of EX527 and PAX more effectively impairs breast cancer cell growth compared to individual treatments. However, further investigations are required to clarify the specific targets and molecular mechanisms underlying the activity of EX527:PAX in other preclinical models.